The Use Of Seal In Early Malay Official Letters : A Personal Identity And Ethnic Culture - Abdul Razak Karim (JURNAL ARBITRER, 2018)
This brief article discuss on how the seals that were used on the official Malay letters incorporated and displayed the identity of the senders, whether they are individual dignitaries or governments. The early Malay seals are among the symbol and identity of the sender. In the traditional Malay society the seal was not something that anyone can own and use indiscriminately. The seals were used as personal symbols by the individual rulers and dignitaries and subsequently became something that was passed on as part of their inheritance. For an individual sultan or dignitary, the seal represented and displayed his identity. The concept of identity in relation to the early Malay official letters is actually the Malay identity. This article also discuss the shape and form of seal, the language used, and .calligraphy or artistic writing style.